User innovativeness and Fintech adoption in Indonesia - Budi Setiawan; Deni Pandu Nugraha; Atika Irawan; Robert Jeyakumar Nathan; Zeman Zoltan (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The integration of the financial industry and financial technology (Fintech) plays a pivotal role in increasing financial services reach and inclusion for the large unbanked population in Indonesia. Fintech adoption optimization expands the financial access to formal financial institutions, especially to vulnerable groups such as the unbanked population who predominantly reside in rural areas far from formal financial institutions. Fintech is viewed as a game changer to bring finance to the unreached communities via information technology and digital financial landscape. In this causal research, data collection was done via online questionnaires to 485 Fintech users between December 2020 and April 2021. Data analysis and path modelling was performed using smartPLS 3.0 software. Result shows user innovativeness as a significant predictor, directly and indirectly affecting the adoption of Fintech in Indonesia, while user attitude found the most important factor towards Fintech adoption. Financial literacy is the least important variable to predict Fintech adoption, contrary to popular belief. This indicates that Fintech usage requires less financial literacy and is potential to reach unbanked population and those with low financial literacy. To make Fintech more inclusive, the government needs to accelerate improving Information and Communications Technology (ICT) infrastructure such as widening mobile broadband penetration and soft infrastructure by encouraging Fintech startup, allowing regulatory sandbox for startups, and driving financial institutions to innovate through Fintech to bring financial services to unbanked population.
Keywords: 650; financial technology; attitude; financial literacy; individual innovativeness; unbankedpopulation; Sustainable Development Goal 8